Penyuluhan Bahan Kimia Berbahaya melalui Piktogram Globally Harmonized System (GHS) dan Safety Data Sheet (SDS) - Piawi, Kiprah; Murwindra, Rosa; Musdansi, Dwi Putri; Irfandi, Irfandi; Ningsih, Jumriana Rahayu; Marthisza, Zelandy Aulia (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Occupational health and safety are an important part of carrying out activities in the laboratory. The Globally Harmonized System (GHS) is a global integrated system for standardizing the classification and labeling of chemicals. In addition, the Safety Data Sheet (SDS) is a safety data sheet that contains information about the safety and instructions for use of each chemical. Practical activities carried out in schools still experience shortcomings in providing understanding to students about this. The counseling activity carried out by the Chemistry Education Study Program, Kuantan Singingi Islamic University was held on May 9, 2025. The method used in this activity is a counseling method supported by a survey. The target of this activity is 17 students of the Syafa'aturrasul Kuantan Singingi Islamic Boarding School. From these activities it can be concluded that (1) The Community Service (PkM) material is in accordance with the needs of participants/partners; (2) Participants/Partners get direct benefits from this activity for safety in working in the laboratory and in daily life; (3) PkM activities are successful in increasing students' knowledge and awareness of how to handle hazardous chemicals. In general, participants are satisfied with activities.ABSTRAKKesehatan dan keselamatan kerja merupakan bagian penting dalam pelaksanaan kegiatan di laboratorium. Sistem Harmonisasi Global (GHS) adalah sistem terpadu global untuk menstandarisasi klasifikasi dan pelabelan bahan kimia. Selain itu, Lembar Data Keselamatan (SDS) adalah lembar data keselamatan yang berisi informasi tentang keselamatan dan petunjuk penggunaan setiap bahan kimia. Kegiatan praktikum yang dilakukan di sekolah masih mengalami kekurangan dalam memberikan pemahaman kepada siswa tentang hal ini. Pengabdian Kepada Masyarakat Prodi Pendidikan Kimia Universitas Islam Kuantan Singingi dilaksanakan pada tanggal 9 Mei 2025. Metode yang digunakan dalam kegiatan ini adalah metode konseling yang didukung oleh survei. Target kegiatan ini adalah 17 siswa Pondok Pesantren Syafa'aturrasul Kuantan Singingi. Dari kegiatan-kegiatan tersebut dapat disimpulkan bahwa (1) Materi Pengabdian Masyarakat (PkM) sesuai dengan kebutuhan peserta; (2) Peserta memperoleh manfaat langsung dari kegiatan ini untuk keselamatan dalam bekerja di laboratorium dan dalam kehidupan sehari-hari; (3) Kegiatan PkM berhasil meningkatkan pengetahuan dan kesadaran Peserta tentang cara menangani bahan kimia berbahaya. Secara umum, peserta PkM merasa puas dengan kegiatan PkM.